Pengaruh Umur Panen Terhadap Kandungan Zat Gizi Biji Dua Varietas Kacang Tanah (Arachis hypogaea L.) - Astuti Hertiningsih (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2003)
The objectives of the research is to study  the influence of harvest time on seed nutrition content of two varieties of peanut. The varieties of peanust are Gajah and Local varieties. The harvest was divided into eight time differences, as follow: 26, 31, 36, 41, 46, 51, 56  and 61 days after flowering. The seed nutrition was measured as carbohydrate, protein,  lipid and water content. The data were analyzed by Anova and DMRT, and quadratic regression.  The research showed that nutrition content of seed is influenced by the time of harvest.